Pengaruh Tipe Kepribadian, Berpikir Divergen, Iklim Keluarga, dan Motivasi Terhadap Prestasi Belajar Matematika Siswa Kelas XI MIPA SMA - Hamzah Upu; Nasrullah; Alim Alqadri Amir (Issues in Mathematics Education (IMED), 2020)
This study was ex-post facto research which purposed to know the influence of personality type, divergent thinking, family climate, and motivation toward student’s mathematics learning achievement on grade XI of Senior High School in Sinjai. The population of this study is student grade 11th MIA Senior High School in Sinjai. The sampling technique in this study was cluster random sampling, so the sample is 60 student grade 11th MIA in Senior High School in Sinjai. The data was collected using a questionnaire and test, then analyzed using descriptive statistics and inferential statistics. The results showed that there was no direct and indirect influence of personality types on students' mathematics learning achievement. In addition, there is a direct influence of each of the motivation, family climate and divergent thinking on the mathematics learning achievement of students. So that the family climate and divergent thinking each have an indirect effect on mathematics learning achievement through motivational variables.